Inovasi Pendanaan Kesehatan untuk Mewujudkan UHC di Indonesia : Literature Review - Raisha Syahidah; Meutya Zahra Eriansyah; Riswandy Wasir (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia continues its efforts to achieve Universal Health Coverage (UHC) through the National Health Insurance (Jaminan Kesehatan Nasional/JKN) program, which faces funding challenges such as financial deficits and reliance on participant contributions. This literature review aims to identify health financing innovations that can support UHC in Indonesia. The study adopts a literature review method, utilizing data sources from Google Scholar covering the period 2016–2025, focusing on relevant studies concerning financing innovations and UHC in Indonesia. The findings indicate that financing innovations, such as increasing excise taxes on unhealthy products and utilizing Corporate Social Responsibility (CSR) funds, hold significant potential. Cross-sector collaboration is essential to expand funding sources and ensure equitable health service delivery. Partnerships between the government, private sector, and communities are crucial for the sustainability of JKN and the achievement of UHC in Indonesia. Further research is recommended to explore the role of non-government sectors in greater depth.